An Augmented Reality Head-Up Display System with a Wide-View Eyebox. (30th June 2020) - Wu, Pei-Jung; Chuang, Chih-Hao; Chen, Chien-Yu; Wu, Jeng-Han; Lin, Bor-Shyh
Abstract : This study proposes to apply the combination of two 90-degree prisms and a holographic optical element to an image-dividing element, divide an image into three through the virtual image projection system, and accurately project the images to 160 cm behind the windshield. In order to distinguish the left image, middle image, and right image at the horizontal direction, the 90-degree prism is first utilized for horizontally deflecting the light, a holographic optical element is then used for presenting the vertical deflection of the image, and finally, the images are horizontally arranged as a real image on the diffuser. An image-dividing element is eventually integrated to the virtual image projection system. Then, the divided images are made as a virtual image which is projected to 160 cm behind the windshield to combine with the street scene. The horizontal angle of view of an eyebox is increased from 2.51° to 7.22°, and the size of the eyebox is 31.68 cm × 12.48 cm, allowing a wide-view laser-based head-up display with the large-angle beam-splitting function being successfully designed. It would not affect the field of view on the road, and this system could reduce the space and be arranged easily in a vehicle. Therefore, this proposed system is suitable for the aftermarket.